Analisis Efisiensi Penggunaan Modal Kerja Terhadap Transaksi Pelayanan dan Transaksi Bisnis Pada Koperasi PT. XYZ Cikarang - Muhamad Iqbal Haryo Pratomo; Muhammad Miftahul Amin; Sutrisno Sutrisno (Peneliti.net, 2021)
The purpose of this research is to better identify whether the working capital turnover of cooperatives has been effective, to identify whether the working capital turnover of cooperatives on service transactions has been efficient, and to find out whether the working capital turnover of cooperatives on business transactions has been effective. Cooperative Working Capital Turnover This ratio is used in this study to measure the ability of the cooperative body in an effort to rotate its working capital, or calculate the working capital ability to generate gross participation and cooperative income from business results with non-members. It was concluded that in 2015 with a ratio of 1,034, the efficiency of working capital in an effort to obtain gross participation and income from business results with non-members was considered effective. From the results we can see that the results of the calculation of the capital turnover ratio in 2017 are equal to 1,088 is considered effective. In 2019 with a ratio of 1,148, for the effectiveness of working capital in an effort to obtain gross participation and income from business results with non-members, it is considered Ineffective. Working Capital Turnover on Service Transactions This ratio is used in this study to measure the level of cooperative ability in rotating its working capital. , or working capital capability for service activities to members and generate gross participation (PB). PMKt a = P MKta = working capital turnover on service and business transactions in a certain year